Catheter-related bloodstream infections in patients with intestinal failure receiving home parenteral support: risks related to a catheter-salvage strategy. Issue 5 (20th April 2018) - Tribler, Siri; Brandt, Christopher F; Fuglsang, Kristian A; Staun, Michael; Broebech, Per; Moser, Claus E; Scheike, Thomas; Jeppesen, Palle B
ABSTRACT: Background: In intestinal failure (IF) patients receiving home parenteral support (HPS), catheter-related bloodstream infections (CRBSIs) frequently result in replacement of their tunneled central venous catheters (CVCs), which may lead to future loss of central venous access. Objective: This observational study investigated the consequences of a catheter-salvage strategy related to CRBSIs. Design: All CRBSIs from 2002 to 2016 in the Copenhagen IF and microbiological databases were retrospectively analyzed. Catheter salvage was defined by successful antimicrobial therapy with a retained CVC at discharge. Re-occurrences of CRBSIs with the same microbial species and identical antibiogram were defined as a relapse (<30 d) or as a recurrent (30–100 d) infection. Cox regression analyses incorporated a frailty factor to account for recurrent events and overrepresentation by some patients. Cumulative incidence curves are presented with a competing risk model. Results: There were 2006 tunneled CVCs inserted in 715 adult HPS patients covering 2014.3 CVC years, with a CRBSI incidence rate of 1.83/1000 ( n = 1350) and a mortality rate of 0.007/1000 CVC days ( n = 5). The mean ± SD salvage rate was 55.3% ± 5.5%, varying according to infection type [monoinfections (62.9% ± 4.4%) and polyinfections (58.6% ± 17.3%)] and causative microorganism [coagulase-negative Staphylococci (CoNS) (68.1% ± 9.4%), Staphylococcus aureus (42.6% ± 17.5%), and Enterobacteriaceae (54.3% ± 16.7%)]. The overall risk of CRBSI relapse was 7.5%, and the risk of CRBSI recurrence was 7.3%. The HR for a subsequent CRBSI was 14% lower in a replaced than in a retained CVC (95% CI: 0.74, 0.99). The HR for a new CRBSI after catheter salvage was 36% higher after polyinfections than after monoinfections (95% CI: 1.03, 1.79). Enterobacteriaceae entailed an increased risk of CRBSI recurrence compared with CoNS (2.26; 95% CI; 1.08, 4.75) and S. aureus (4.45; 95% CI: 1.28, 15.5). Conclusions: High catheter-salvage rates related to CRBSIs were achievable and safe in HPS patients within a broad range of microorganisms but contributed to an increased risk of CRBSI relapse or recurrence.